Czasowe złoża stylowe we współczesnym modlitewniku - Wojtak, Maria (Stylistyka, 2021)
Neologism ‘temporary stylistic deposits’ used in the title allows surmounting the phe- nomenon of stylistic polymorphism of a contemporary prayer book designed for youth in the temporalistic perspective.The author concentrates on two tendencies: stylistic traditionalism (conservatism) and stylistic modemism.The first tendency means reaching for the attributes of the traditional religious style, both in forms of utterances as well as language forms that have existed in religious utte- rances for centuries.The modemisational tendencies are linked to introduction in prayer texts contemporary life realia (computers, the internet), and colloquial or even slang wording.The article affirms the author’s thesis on coexistence in the contemporary religious di- scourse of utterances that have originated in various epochs.